Livestock wastewater treatment using aerobic granular sludge - Othman, Inawati; Nor Anuar, Aznah; Ujang, Zaini; Rosman, Noor Hasyimah; Harun, Hasnida; Chelliapan, Shreeshivadasan (Elsevier, 2013)
The present study demonstrated that aerobic granular sludge is capable of treating livestock wastewater from a cattle farm in a sequencing batch reactor (SBR) without the presence of support material. A lab scale SBR was operated for 80 d using 4 h cycle time with an organic loading rate (OLR) of 9 kg COD m3 - d1 . Results showed that the aerobic granules were growing from 0.1 to 4.1 mm towards the end of the experimental period. The sludge volume index (SVI) was 42 ml g1 while the biomass concentration in the reactor grew up to 10.3 g L1 represent excellent biomass separation and good settling ability of the granules. During this period, maximum COD, TN and TP removal efficiencies (74%, 73% and 70%, respectively) were observed in the SBR system, confirming high microbial activity in the SBR system.